Linguistic presentation of mythological consciousness (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the features of reflection animal names in a language image of the Kazakh and Russian languages. The article comsiders in detail the mythological thinking as an ancient form of social consciousness, forming a special view of the world and nature. The subject of detailed analysis in the article are the connotative meanings of names of animals and ways of interpreting them in the Kazakh and Russian languages. The names of animals, as a special stratum of vocabulary, always serve as a figurative characteristics of a person’s appearance, his way of life, way of thinking, social status. Speaking in characterizing the functions they are able to reveal national-cultural features of their shape-related worldview, linguistic consciousness and cultural traditions of people. Mythological thinking contributes to the disclosure of data features, revealing a cultural code in a metaphorical understanding of animal names.
Keywords: mythological thinking; names of animals; linguistic consciousness; symbolic meanings; Slavic mythology; Turkic mythology; metaphors.